High Sensitive C-Reactive Protein as a Marker of Systemic Inflammation in Male Coronary Artery Disease with Obstructive Sleep Apnea - Allen Widysanto; Audrey Suryani Soetjipto; Michelle Widysanto (Jurnal Respirologi Indonesia, 2021)
Background: High Sensitive C-Reactive Protein (hsCRP) is an acute phase protein which may be used as a sensitive marker for increased risk of cardiovascular events in Obstructive Sleep Apnea (OSA) subjects. Methods: This was a cross-sectional study to evaluate hsCRP as a sensitive marker for cardiovascular events in Obstructive Sleep Apnea (OSA) subjects. Subjects were recruited at Medical Check-up Department, Siloam Hospital Lippo Village, Karawaci, Tangerang between January and December 2018. This study included 74 OSA men whose blood were collected after fasting prior to hsCRP test. The diagnosis of Coronary Artery Disease (CAD) was determined by previous medical examinations using treadmill test, CT angiography and cardiac catheterization. Results: There were 39 people (52,7%) who were diagnosed with CAD out of 74 OSA men. The cut off point for hsCRP more than 0,42 was a marker for increased risk for CAD with Odds Ratio (OR)=7,43, Relative Risk (RR)=88%, sensitivity=17,95%, specificity=97,14%, Likelihood ratio (LR+) 6,28 and LR(-) 0,84. Conclusion: HsCRP with cut-off point >0,42 could be used as a marker of increased risk of cardiovascular case in male OSA subjects.